(untitled) (Research, Society and Development, 2021)
Introduction: plant based medicines holds important contributions to society since ancient times. Its use must be conducted cautiously, in addition, efficiency should be proven and toxicity should be measured to avoid adverse post-consumer reactions. Therefore, the Cissus sicyoides that is popularly known as cipó-pucá, insulina vegetal, uva brava and cortina japonesa, is used for presenting antidiabetic, anti-inflammatory, antimicrobial, and antidiarrheal activities among others. Therefore, scientific tests are necessary to evaluate possible cytotoxicity and biological activities. Objective: to evaluate the possible toxicity, phytochemical characterization and biological potentials of the plant. Methodology: The study was carried out through phytochemical analysis and free radical elimination trials, in vitro photo protective activity, hemolytic activity and cytotoxicity against Artemia salina. Results: the phytochemical analysis was positive for alkaloids, flavonoids, saponins, polyphenois (hydrolysable tannins), terpenes and steroids. However, cytotoxicity trails show low LC 50 bioactivity against Artemia Salina L. and elevated hemolytic activity. As for spectrophotometric absorption aspects, a photo protective potential was evidenced. Conclusion: farther studies are suggested to determine other biological potentials, possibly contributing to the development of new drugs, where they can be applied in therapeutic activities involving cytotoxicity, such as antitumor and antimicrobial.